Isolation and screening of potential bacteria with biofilm formation ability and their hydrolytic enzymes for enhanced biogas production - Fazil, Nurul Alia; Alam, Md. Zahangir; Azmi, Azlin Suhaida; Mansor, Mariatul Fadzillah (Universiti Sains Malaysia (USM), 2017)
Biofilm mediated anaerobic digestion of POME are to be studied to produce biogas. Out of 120 strains isolated from palm oil mill effluent (POME), palm kernel cake (PKC), and food waste compost, only 13 strains showed biofilm producing ability with significant amount at OD595nm (>0.01). In hydrolytic enzyme assay test, which are amylolytic enzyme assay, cellulolytic enzyme assay, lipolytic enzyme assay, and proteolytic enzyme assay all strains does not secrete protease enzyme, and strain number 1C and 23 does not secrete any hydrolytic enzymes. Strain number 23C and 30C shows positive result for cellulase, amylase and lipase enzymes to be tested as single strain bacteria for prospect research on producing biogas while other strains will be treated as mixed culture in future research.